Tantangan Dan Strategi Kewirausahaan Mahasiswa Pada Ekonomi Berbasis Inovasi: Penelitian - Nur Milla; Adibatul Humairoh; Riska Sonjaya; Titi Herliani; Idham Kholid (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study highlights a strategic issue concerning the challenges and strategic measures of student entrepreneurship within the rapidly evolving innovation-driven economy in the digital era. Although students’ enthusiasm for entrepreneurship continues to increase, several fundamental obstacles persist, including limited access to capital, insufficient managerial experience, weak institutional support, and low innovative capacity among students. The study aims to identify the key challenges encountered and to formulate effective strategies recommended in academic literature to strengthen the entrepreneurial ecosystem among university students. The research employed a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework, involving a systematic analysis of scholarly articles indexed in Scopus, Web of Science, and Google Scholar between 2015 and 2025. The findings indicate that the most effective strategies include the implementation of experiential learning, cross-sector collaboration through the triple helix model, utilization of digital technologies, and the integration of mentoring programs and business networking reinforcement. Conceptually, the study affirms that the success of student entrepreneurship is strongly influenced by an innovative ecosystem supported by universities, industry, and government. The conclusions suggest that a systemic and collaborative approach is required to address the multidimensional challenges faced by student entrepreneurs. In terms of practical implications, the study underscores the need for higher education policy reform and the strengthening of universities’ roles as innovation catalysts to foster a generation of young entrepreneurs who are adaptive, creative, and competitive within a knowledge-based economy.